(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The topic of branding is extremely important for all sectors of the economics. Building a brand of tourist destination is a painstaking, long-standing and multi-stage process. Many factors contribute to improving tourism performance. One of the most significant is the informational promotion of a tourist destination. The task of Мedia-channels is to inform and convince, doing it with a certain frequency.